2018
DOI: 10.19082/6448
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tooth value and skin color in patients visiting Royal Medical Services clinics of Jordan

Abstract: BackgroundFacial and dental aesthetics are becoming of great concern for patients, especially for the younger generation. Tooth color matching and selection is considered a vital element in order to create an attractive beautiful smile. The importance of tooth color matching is to adjust tooth colors to obtain a good match with adjacent teeth and the skin. This is considered a challenge especially if adjacent teeth were lost or records of patients’ teeth color were not available.ObjectiveThe aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…Patients with fair skin are more prone to have teeth with low L* values, while those with dark skin are more likely to have teeth with high L*values. 76,77 The observer's shade matching ability impacts shade selection results. This ability may be affected by age, gender, experience, type of shade guide, training, color perception potentials, and diseases.…”
Section: Effective Factors and Conditions Related To Visual Methodsmentioning
confidence: 99%
“…Patients with fair skin are more prone to have teeth with low L* values, while those with dark skin are more likely to have teeth with high L*values. 76,77 The observer's shade matching ability impacts shade selection results. This ability may be affected by age, gender, experience, type of shade guide, training, color perception potentials, and diseases.…”
Section: Effective Factors and Conditions Related To Visual Methodsmentioning
confidence: 99%
“…Thus this correlates with studies of tooth colour are conducted in relevance to colour of skin, age or sex (Susanty et al, 2018). However results of similar studies can vary from one case to another and probably their consistency depends on different factors such as analysed population (Lagouvardos et al, 2012;Al-Nsour et al, 2018;Tancu et al, 2019). It is worth mentioning that soft tissue colourimetry is a matter of study in dentistry as well, and this can be a feature to consider in anthropological reconstruction in line with dental shade study results (Hyun et al, 2016).…”
Section: Related Workmentioning
confidence: 65%
“…Nevertheless, even under the right conditions, the traditional colour matching procedure preserves a certain degree of subjectivity as colour perception remains an individual feature (Shooriabi et al, 2016). Thus in recent decades a number of devices improving and facilitating shade matching in dentistry have been designed (Brewer et al, 2004;Al-Dwairi et al, 2014). Thus conventional spectrometers and spectrophotometers are a better match for digital reconstructions of teeth which represent our study material.…”
Section: Related Workmentioning
confidence: 99%
“…For the canines, B3 was most observed for the youngest two groups and A3.5 for the oldest two groups [11]. A study conducted in Jordan comparing tooth shade to skin color revealed that Jordanians have a light tooth value and that people with a dark skin complex have lighter teeth [12]. The skin color of an individual might help the prosthodontist in picking the artificial teeth shade in case of a complete denture [8].…”
Section: Introductionmentioning
confidence: 99%